ANALISIS FAKTOR YANG MENDORONG TINGKAT PUBLIKASI HASIL PENELITIAN DOSEN - Sri Rahmawati Fitriatien; Ibut Priono Leksono (LPPM Universitas Bina Bangsa, 2024)
The productivity of scientific publications from the research results of Universitas PGRI Adi Buana Surabaya lecturers for the last two years has decreased, marked by rankings on both national and regional assessment scales. One of the obstacles that become a downgrade for lecturer performance assessments in the form of lecturer research outputs is that the output-based performance ecosystem in the field of higher education tridharma in research activities has not been achieved. Therefore, this study aims to determine the factors that encourage and the dominant factors on the level of publication of research results by lecturers at Universitas PGRI Adi Buana Surabaya. This type of research is quantitative research using factor analysis involving 105 research subjects using 10 metric attributes. Factor analysis is able to reduce 10 metric attributes into 3 main components which are the driving factors for the level of publication of lecturer research results